Pattern Of Tobacco and Alcohol Use Among Elderly Population in A Rural Area Of Andhra Pradesh, India - Udayar, Sharvanan E; Ashok, Praveen B; Arun D; Sravan, Sai (National Journal of Community Medicine, 2015)
Background: Tobacco and alcohol consumption are the leading cause of preventable death. Fewer studies have focused on tobacco and alcohol use among rural elderly. Objective of the study was to find out the prevalence of tobacco and alcohol use among rural el- derly population and its association with various sociodemo- graphic factors. Method: Cross-sectional community based study was conducted in the rural area of V.Kota mandal of Chittoor district, Andhra Pra- desh. Studyparticipants were selected using multistage random sampling method. Results: The prevalence of current tobacco users was 40.5%, among them 37.2% men and 1.4% women were current smokers. Among tobacco chewers 37.3% were women and 17.3% were men.Alcohol consumption was seen in 28.7% of the men compared with 0.9% of the women.Tobacco and alcohol use was significantly associated with age, education, economic status, marital status and living ar- rangements. Conclusion: There is a high prevalence of smoking and alcohol consumption among men in this rural elderly population which needs to addressed immediately to prolong health living years.